Tourist Loyalty In Bali Green Villages: A Planned Behavior Perspective - I Nyoman Satya Paramartha; Ni Luh Wayan Sayang Telagawathi; Komang Endrawan Sumadi Putra (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study investigates the psychological determinants of tourist loyalty in Green Tourism Villages across Bali Province through the lens of the Theory of Planned Behavior (TPB). Despite the proliferation of community-based green tourism initiatives, repeat visitation rates remain suboptimal, threatening the long-term sustainability of these enterprises. Using a quantitative survey of 384 domestic and international tourists who visited Green Tourism Villages in Bali, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that attitude toward environmentally friendly behavior exerts the strongest influence on behavioral intention (β = 0.421, p < 0.001), followed by subjective norms (β = 0.312, p < 0.001) and perceived behavioral control (β = 0.287, p < 0.001). All three determinants also demonstrate significant direct effects on tourist loyalty. Importantly, behavioral intention partially mediates the relationships between all three TPB determinants and tourist loyalty. The findings advance theoretical understanding of loyalty formation in sustainable tourism contexts by extending TPB to a multidimensional loyalty construct within a collectivist cultural setting. This study offers practical guidance for destination managers to design psychologically informed strategies that cultivate favorable attitudes, leverage social influence, and enhance perceived control to foster enduring tourist loyalty.